Hyperlipidaemia in Asthmatic Patients Receiving Long-term Steroid Therapy - El-Shaboury, A. H. (1973)
Plasma lipids were measured in 100 female asthmatic patients receiving long-term steroid therapy. A significant increase in the incidence of endogenous hypertriglyceridaemia but not of hypercholesterolaemia was found. The hypertriglyceridaemia was not due to obesity or diabetes. Neither the dose of steroid, duration of therapy, nor the addition of corticotrophin gel or depot tetracosactrin influenced the prevalence of hypertriglyceridaemia.